Pin-ended press-braked S960 ultra-high strength steel angle section columns : testing, numerical modelling and design - Wang, Fangying (2022)
The structural performance and compression resistances of pin-ended press-braked S960 ultra-high strength steel (UHSS) angle section columns have been studied based on experiments and numerical modelling, and are reported in the present paper. An experimental programme was firstly performed on two series of press-braked S960 UHSS angle section column specimens, with each series containing six specimens of the same cross-section dimension but different member lengths, and included initial torsional and global geometric imperfection measurements and pin-ended column tests. The detailed pin-ended column test setup, procedures and results, including the failure loads, deformations at the failure loads, load–mid-height lateral deflection curves and failure modes, were fully reported. It is worth noting that two distinct flexural buckling orientations about the minor principle axis were observed from the tests, namely ‘C’ orientation (indicating that the failed column specimens buckled towards the angle corners) and ‘reverse C’ orientation (signifying that the failed column specimens buckled towards the angle tips). A numerical modelling programme was then followed; finite element (FE) models were firstly developed to replicate the test responses, and then adopted to perform parametric studies to generate further numerical data over a wide range of cross-section dimensions and member lengths. Given that the current design codes for steel structures, as used in Europe, Australia/New Zealand and North America, are only applicable to members and joints with material grades up to S700 (or S690), the relevant codified design provisions for press-braked S700 (or S690) high strength steel angle section columns were evaluated for their applicability to press-braked S960 UHSS angle section columns, based on the obtained test and numerical data. The evaluation results revealed that the European code yields unduly conservative and scattered compression resistance predictions when applied to press-braked S960 UHSS angle section columns, while the Australian/New Zealand standard and North American specification lead to a higher degree of design accuracy and consistency, on average, when used for press-braked S960 UHSS angle section columns, though some of the compression resistance predictions are unsafe for those failing by flexural buckling in the ‘C’ orientation.